PERSEPSI TERHADAP PENERAPAN UJI KOMPETENSI NERS INDONESIA (UKNI) MELALUI EXIT EXAM PADA MAHASISWA PENDIDIKAN PROFESI NERS - Putri Mayasari; Virza Marsaroza (Fakultas Keperawatan, Universitas Riau, 2023)
The nurse profession takes a competency exam to obtain a Registered Certificate that required by nurses to work in providing nursing care to patients. The UKNI implementation process was carried out after graduates obtained a Nurse degree, but now as exit exam enacted, students are required to pass UKNI for obtaining a Nurse degree, this is still a pro and contra. This was a quantitative research and used exploratory descriptive using a questionnaire from Google form to 93 students of the Nursing Professional Study Program, Faculty of Nursing, Universitas Syiah Kuala in the 2018/2019 academic year (the Exit Exam has not yet been enacted), and 112 students who took part in UKNI February 2023. This study aimed to determine respondent’s perceptions of UKNI before and after the Exit Exam applies in Indonesia. The sampling technique was carried out using accidental sampling. The research was conducted in 2 phases on July 2019 and January 2022 – February 2023. Data analysis using descriptive statistics. The 93 respondents who had not yet had an exit exam showed that the three indicators were in the Disagree category (Purposes and benefits (51.7%), Implementation Principles ( 55.9%), and Formulation of Questions (64.1%), while the other 112 respondents indicated that the three indicators were in the Agree category (Purposes and benefits (63.4%), Implementation Principles (59.8%), and Preparation Question (53.6%) The study results howed that there are differences in respondents' perceptions of implementing UKNI through the exit exam. Probably exit exam is not a difficult thing and running well now. However, preparation is needed from students and institutions to improve competent graduates.